2003
DOI: 10.1007/s11664-003-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth of an intermetallic compound layer with Sn-3.5Ag-5Bi on Cu and Ni-P/Cu during aging treatment

Abstract: Growth kinetics of intermetallic compound (IMC) layers formed between the Sn-3.5Ag-5Bi solder and the Cu and electroless Ni-P substrates were investigated at temperatures ranging from 70°C to 200°C for 0-60 days. With the solder joints between the Sn-Ag-Bi solder and Cu substrates, the IMC layer consisted of two phases: the Cu 6 Sn 5 (η phase) adjacent to the solder and the Cu 3 Sn (ε phase) adjacent to the Cu substrate. In the case of the electroless Ni-P substrate, the IMC formed at the interface was mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…However, as the aging time prolongs, Cu 3 Sn was found as well (easier to be observed at larger magnification shown in Fig. 5) and the solder structure from solder to substrate is SAC solder/Cu 6 Sn 5 /Cu 3 Sn/Cu, which is in accordance with the previous studies [18]. Laurila et al [19] pointed out that in high-temperature conditions (close to 220°C), the Cu-Sn interface reaction is based on the diffusion of Sn, thus presenting a thick Cu 6 Sn 5 interface layer.…”
Section: Interfacial Microstructuresupporting
confidence: 91%
“…However, as the aging time prolongs, Cu 3 Sn was found as well (easier to be observed at larger magnification shown in Fig. 5) and the solder structure from solder to substrate is SAC solder/Cu 6 Sn 5 /Cu 3 Sn/Cu, which is in accordance with the previous studies [18]. Laurila et al [19] pointed out that in high-temperature conditions (close to 220°C), the Cu-Sn interface reaction is based on the diffusion of Sn, thus presenting a thick Cu 6 Sn 5 interface layer.…”
Section: Interfacial Microstructuresupporting
confidence: 91%
“…The electroless Ni-P layer contained about 15at.%P and had an amorphous structure. 17 The electroless Ni-P plating deposits a mixture of Ni and phosphorous (P), because of the use of hypophosphite in the chemical reaction for reducing Ni ions. These solder balls were bonded to the BGA substrate in a reflow process employing rosin mildly activated flux in a reflow machine (SAT-5100 ϩ profile temperature raise heater, Rhesca Co., Hino City, Japan) with a maximum temperature of 255°C for 1 sec (Fig.…”
Section: Solder Ball Attachmentmentioning
confidence: 99%
“…Advantages of the electroless Ni plating such as low stress, excellent corrosion resistance, uniform thickness, and selective deposition make the electroless Ni plating more suitable to be a diffusion barrier than the electroplated Ni and expensive vacuum deposition of Ni. 11,17 However, it has been reported that reliability degradation occurs at the interface between plated electroless Ni layer and solder when a P-enriched (Ni 3 P) layer is formed on the interface during soldering. 18,19 In this study, the reaction of three Pb-free solder alloys (Sn3.5Ag, Sn3.5Ag0.75Cu, and Sn3Ag6Bi2In) on electroless Ni-P layer is characterized.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, Ni is used as a diffusion barrier over copper. 5 Many studies have been performed on the interfacial reactions between Sn-Zn solder and Ni/Cu substrate during reflow and aging. [6][7][8][9][10] It has been observed that Ni prefers to react with Zn over Sn, and forms Ni-Zn compounds in the IMC.…”
Section: Introductionmentioning
confidence: 99%